新媒体与当代中国产品行销 ：李佳琦的网络直播 = New media and product marketing in contemporary China : a study of Li Jiaqi's live streaming - 林欣恩 Lim, Grace Xin En (Nanyang Technological University, 2022)
随着网络技术的迅速发展，旧式的媒体开始有了新的变化。时代的发展促使世界的媒体由传统转化为新式，其中所产生出来的媒体形式为“新媒体”。大量新媒体的涌现对传统的营销模式形成了的冲击与挑战。新媒体当中包括网络直播，而这种新媒体模式因各种优势在产品行销的领域中占据了重要的地位。在众多种新媒体当中，直播是具有强烈影响力的一种新颖、多元化的媒介，其中的直播主也是此行业的核心。在直播中，主播如何与观众互动，将自身的优势发挥得淋漓尽致，以及所实行的有效又吸引人的策略成为了至关紧要的关键。备受瞩目的中国网络直播主李佳琦成功掌握直播主所需的条件，获得“口红一哥”的封号，建立起了成功的直播事业。本文将以新媒体环境下，李佳琦的网络直播为例，通过对其行销策略进行研究，探究李佳琦通过直播所涉及的群众以及获得的盈利，并且分析直播中的问题、改变以及未来的发展。With the rapid development of the Internet and its technology, traditional forms of media have begun to metamorphosise and undergo new changes. The development of the times has led to the transformation of media forms from traditional to contemporary, resulting in the formation of "new media". New media has continued to assert dominance in society over the past years, forming a greater impact and challenge on the marketing model of traditional enterprises. A form of new media includes live streaming, and this approach owns an influential position in the field of product marketing due to its various advantages. Among the many types of new media, live streaming is a novel and diversified medium with strong influence. In this new media approach of live streaming, the live streamer plays a core role. In the realm of the live streaming industry, the way in which the live streamer interacts with their audience, exhibits their marketable points, and implements effective and eye-catching strategies are all critical components for success. The high-profile Chinese live-streamer Li Jiaqi successfully mastered the requisites of live streaming, has been bestowed the title of "Lipstick Brother", and has established a successful live streaming career. This article will be focused on Li Jiaqi’s live streaming career in the new media environment, seeking to analyse the impacts of the product marketing strategies used by himself and his team on product sales, his target audience and revenues earned through live streaming, as well as to analyse the problems, changes and potential future endeavours.